Triangulos Triangulos a nuestro alrededor - Schuette, Sarah L; Ferrer, Martin Luis Guzman (Mankato, Minn : Capstone press, 2010)
"Simple text, photographs, and illustrations show triangles in everyday objects--in both English and Spanish"--Provided by publisher
Arithmetic notions
Text avilable in English and spanish
1 2 13
NEW_ZTN_GN
Keywords: Spanish language materials -- Bilingual; Triangle -- Juvenile literature; Triangle